2.1k views
13 votes
Which expression will give you the phase shift when the standard form is f left parenthesis x right parenthesis equals a sine left parenthesis b x plus c right parenthesis plus d?

User NateJ
by
6.3k points

1 Answer

3 votes

Answer:


Phase\ Shift = -(c)/(b)

Explanation:

See comment for complete question

Given


f(x) = Asin(bx+c)+d

Required

Determine an expression for the phase shift


f(x) = Asin(bx+c)+d

Factorize the expression in bracket


f(x) = Asin(b(x+(c)/(b)))+d

The general expression is:


F(t) = A f(B(t - C/B)) + D

Where:

C/B is the phase shift

By comparing the general expression with:
f(x) = Asin(b(x+(c)/(b)))+d


-(C)/(B) = (c)/(b)

Multiply both sides by -1


(C)/(B) = -(c)/(b)

Hence:


Phase\ Shift = -(c)/(b)

User Jawann
by
6.2k points